Utilitization Of Catfish Bone Gelatin (Pangasius Sp.) In Marshmallow Products - Catur Pramono Adi; Sukma Budi Prasetyati; Elvi Andriani Br Sebayang; Aripudin Aripudin (Barakuda'45, 2022)
To take advantage of the by-product of catfish bone, gelatin is made as a value added of the by-product of the fishery industry, because Gelatin using sapa bovine fish bone has the same characteristics as catfish bone gelatin. Gelatin is the main ingredient in the manufacture of marshmallows to improve texture and ebilite. The purpose of this study was to determine the panelists' preference for marshmallows with the addition of catfish bone gelatin into marshmallows and to conduct chemical quality tests (water content and ash content) on catfish bone gelatin marshmallows. The method used is descriptive method, the results of this study are marshmallow hedonic testing with the highest appearance parameter value found in the sample F2 = 7.54, namely the addition of 0.93 gram catfish bone gelatin. From the parameters of taste, aroma, and texture, the highest value was found in sample F3 with the addition of 1.16 gram catfish bone gelatin to get a taste parameter value of 7.72, an aroma parameter value of 7.52, and a texture parameter value of 7.66. In chemical testing, all samples met the standard of SNI 3547.2-2008 soft confectionery. In the water content parameter, the highest value was found in sample F2 of 11.85% with a maximum limit of SNI 3547.2-2008 soft confectionery 20.0%. In the ash content parameter, the highest value is found in the F2 sample of 0.455% with a maximum limit of 3.0%. In the protein parameter, the protein test was taken from the best sample of sensory test results, namely marshmallow with the addition of 1.17gram catfish gelatin and 2.34gram beef gelatin with a protein content test result of 0.315%